دراسة الفعل الحراري الناتج عن تفاعل استبدال شوارد الكلوريد بشوارد البروميد في معقد الذهب AuCl4‾ ] [ (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث دراسة الفعل الحراري لمزيج كيميائي متفاعل بشكل متتالي وذلك من خلال تفاعل استبدال شوارد الكلوريد بشوارد البروميد في معقد الذهب −AuCl4. تم استخدام مسعر الناقلية الحراري الذي يحتوي على مزدوجتين حراريتين والموصول مع جهاز غلفانومتر بدوره موصول مع راسم يسجل المنحني البياني الناتج عن الأفعال الحرارية الناجمة عن تفاعل الاستبدال موضوع البحث. بعد حساب مساحة السطح البياني الذي يمثل التغير في مقدار انحراف الغلفانومتر بتابعية الزمن، تم حساب كمية الحرارة الكلية الناجمة عن التفاعل الكيميائي الحاصل في خلية المسعر الحراري، إذ إنّ جزءاً من كمية الحرارة يتم فقدانه على شكل انتشار حراري، والجزء الآخر يؤدي إلى ارتفاع درجة حرارة الوعاء الداخلي للمسعر بمقدار Δθ خلال زمن مقداره tΔ. تمت دراسة الفعل الحراري لتفاعل استبدال شوارد الكلوريد بشوارد البروميد من أجل نوعين من المحاليل كوسط للتفاعل، الأول يحتوي على ملح NaClO4 والثاني ملح KNO3 [1]، بعد حساب كميات الحرارة الناتجة عن تفاعل الاستبدال في الوسطين المختلفين تبين أن الفعل الحراري في وسط من NaClO4 أكبر من الفعل الحراري في وسط من KNO3. This research studies the thermal action for a chemical mixture gradually reacting through the reaction of replacing Chloride Ions by Bromide Ions in . A calorimeter for thermal transmission containing two thermal couples has been used; and it was connected to galvanometer, which in turn connected to diagram recorder of the graph resultant from the thermal actions coming from the replacement reaction, which is the subject of the research. After calculating the area of the resultant graphic surface, the total thermal quantity coming from the chemical reaction within the calorimeter cell has been calculated as well; whereas part of the thermal quantity would be lost in the form of thermal diffusion. The other part would lead to the rise of temperature in the thermal vessel of the calorimeter by q during a period of Dt. The study of the thermal action for the reaction from replacing Chloride ions by Bromide ions has been made for two kinds of solutions. The first contains NaClO4 and the second KNO3 [1]. After calculating the thermal quantities coming from replacement action in the two different media, it has been found that the thermal action in NaClO4 medium is higher than the thermal action in KNO3 medium; that is, there is a role for those added salts affecting the thermal action resulting from the studied reaction.